The influence of employment modes on employee turnover and agri-business performance: a case for Hunyani farm in the Zvimba district, Zimbabwe - Kudakwashe Svotwa (Apstract: Applied Studies in Agribusiness and Commerce, 2019)
The labour intensive nature of Zimbabwean agriculture demands that farmers meet excessive labour requirements, at the same time keeping labour costs as low as possible to guarantee profits and achieve maximum business performance. This study, carried through a questionnaire survey, at the Hunyani Matura Farm, in the Zvimba district of Zimbabwe between from October 2017 to March 2018, investigated the effect of employment mode on turnover and agri-business performance. Data collected from the participants, was compared with the information from secondary source documents. From the results temporary workers performed better than permanent workers and they cited problems of low wages, poor working conditions, high work targets, inequality in work allocation, job insecurity and constant shuffling. Temporary workers had higher turnover and turnover intentions than permanent workers. Temporary employment mode had a positive effect on agri-business performance. This study recommends the use of permanent employment mode on key positions like forepersons, stores persons and supervisors, and temporary employment mode on general farm tasks, while seasonal contracts were seen good for skill demanding operations such as tobacco seedbed establishment, tobacco reaping and curing and grading. A ccareful selection of employment modes reduces inequalities and unhealthy attitudes at work and improves on farm business performance.